Synthesis of microcrystalline cellulose from pretreated cotton obtained from Bombax ceiba L. and its characterization (Bangladesh Journal of Scientific and Industrial Research, 2015)
Microcrystalline cellulose (MCC) is an important ingredient in pharmaceutical, food, cosmetic and other industries. Microcrystalline cellulose was synthesized from the alpha cellulose content of pretreated cotton, Bombax ceiba L. by hydrochloric acid hydrolysis. The prepared microcrystalline cellulose was characterized by determining some physicochemical properties such as pH, angle of response, Carrs index, Hausner ratio, moisture content etc and compared with commercial-grade microcrystalline cellulose that is used in pharmaceutical industry as excipient. Scanning electron microscope (SEM) and FTIR data represented the structure and particle characterization of sample. Thermal gravimetric analysis (TGA) showed the thermal stability of the sample. The results showed that the yield of microcrystalline cellulose was about 85% and compared favorably with the commercial grade microcrystalline cellulose as well as conformed official specifications for microcrystalline cellulose in British Pharmacopeia. It was also found that the duration of acid hydrolysis affected the polymeric form of the processed alpha cellulose.Bangladesh J. Sci. Ind. Res. 50(3), 199-204, 2015